Characteristics of Inconel Powders for Powder-Bed Additive Manufacturing. (October 2017) - Nguyen, Quy Bau; Nai, Mui Ling Sharon; Zhu, Zhiguang; Sun, Chen-Nan; Wei, Jun; Zhou, Wei
Abstract: In this study, the flow characteristics and behaviors of virgin and recycled Inconel powder for powder-bed additive manufacturing (AM) were studied using different powder characterization techniques. The results revealed that the particle size distribution (PSD) for the selective laser melting (SLM) process is typically in the range from 15 μm to 63 μm. The flow rate of virgin Inconel powder is around 28 s·(50 g) −1 . In addition, the packing density was found to be 60%. The rheological test results indicate that the virgin powder has reasonably good flowability compared with the recycled powder. The inter-relation between the powder characteristics is discussed herein. A propeller was successfully printed using the powder. The results suggest that Inconel powder is suitable for AM and can be a good reference for researchers who attempt to produce AM powders.